Evidence Based Scarce Resource Allocation During the COVID-19 Pandemic: A Case Study of Bamlanivimab Administration in the Emergency Department. (October 2022) - Rozycki, Elizabeth; Weiner, Ashley; Malvestutto, Carlos; Kman, Nicholas E; Lustberg, Mark; Dick, Michael; Lehman, K. Joy; Schieber, Ariane; Luca, Lynne; Jordan, Trisha A; Reed, Erica E; Allen, James; et al.
Background: Patients presenting for emergency department (ED) evaluation may be appropriate for treatment with monoclonal antibodies for mild to moderate COVID-19. While many sites have implemented infusion centers for these agents, EDs will continue to evaluate these patients where appropriate identification and efficient infusion of eligible patients is critical.Objectives: Patients receiving bamlanivimab in the EDs of an academic medical center are described. The primary objective was to describe operational metrics and secondary objectives reported clinical outcomes.Methods: Patients receiving bamlanivimab and discharged from the ED were included from November 16, 2020 to January 16, 2021 in the retrospective, observational cohort. Primary outcome was adherence to institutional criteria. Secondary outcomes included ED visit metrics, clinical characteristics, and return visits within 30 days. Risk factors for return visits were assessed with regression.Results: One hundred nineteen patients were included. Most (71%) were diagnosed with COVID-19 during the ED visit and median symptom duration was 3(IQR 2-5) days. Median number of risk factors for progression to severe disease was 2 (IQR 1-2). Thirty percent had a documented abnormal chest x-ray. Institutional criteria adherence was 99.2%. Median time from ED room to bamlanivimab was 4 (IQR 3.1-5.2) hours. Thirty patients had return visit within 30 days; 19 were COVID-19 related. Two multivariable regression models were analyzed for COVID-19 related return visit. Characteristics on ED presentation were considered in Model I: male gender (OR 3.01[0.97-9.31]), age (per 10 years) (OR 1.49[1.05-2.12]), African-American race (OR 3.46[1.09-11.06]), and symptom duration (per day) (OR 1.34[1.05-1.73]). Model II included labs and imaging acquired in ED. In Model II, age (per 10 years) (OR 1.52[1.07-2.16]) and abnormal CXR (OR 5.74[1.95-16.9]) were associated with COVID-19 related return visits.Conclusions: Administration of bamlanivimab to ED patients can be done efficiently, with the potential to reduce COVID-19 related return visits. Age and abnormal imaging were independent predictors of COVID-19 return visits.